Customized Hook Plates for Metaphyseal Fractures, Nonunions and Osteotomies in the Dog and Cat - Robins, G. M.; Eaton-Wells, R.; Johnson, K. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The use of customized DCP plates, to achieve stable fixation, is demonstrated to be possible in situations where a normal plate configuration does not allow for an adequate number of screws to be inserted. This report documents the use of customized hook plates in ten such cases.
Keywords: Customized hook plate; metaphyseal fractures